Collaborative Approaches to Enhancing Maternity Care: Interdisciplinary Management of Common and Emerging Critical Health Issues (Asian Journal of Pharmaceutics (AJP), 2025)
Most of us would agree with the statement that pregnancy and childbirth are some of the most vulnerable phasesin a woman’s life and women’s safety and maternity care heavily affects the maternal mortality rate and neonatalmortality rate. A well-developed caregiving system can help mother’s combat challenges, such as pre-eclampsia,gestational diabetes, and the safety of medication during breastfeeding. The analysis of this study focused onthe participation of healthcare professionals, including doctors, midwives, nurses, and pharmacists, with the useof technologies, such as telemedicine, and centralized communication platforms. These include role ambiguity,communication challenges, and cultural hierarchies. Interdisciplinary approaches to delivery improved maternalcare. Reduced complications and better patient outcomes ensued. Centralized systems eradicated errors, whilegood teamwork resolved issues with safety concerning maternal immunization and breastfeeding. Professionalhierarchies and workload pressures were still problems. Nurses and pharmacists played key roles in mitigatingmedication-related risks. Communication frameworks and mutual respect also fostered collaboration. Roledefinition, training programs together, and an equitable distribution of workload must be present to overcome thebarriers. Interdisciplinary collaboration is important for holistic maternity care. Empowerment of the health teamsby technology, training, and streamlining will help improve maternal outcomes sustainably.